Brain injury, neuroinflammation and Alzheimer's disease - Breunig, Joshua; Guillot-Sestier, Marie-Victoire; Town, Terrence (Frontiers in Aging Neuroscience, 2013)
With as many as 300,000 United States troops in Iraq and Afghanistan having suffered head injuries (Miller 2012), traumatic brain injury (TBI) has garnered much recent attention. While the cause and severity of these injuries is variable, severe cases can lead to lifelong disability or even death. While aging is the greatest risk factor for Alzheimer’s disease (AD), it is now becoming clear that a history of TBI predisposes the individual to AD later in life (Sivanandam and Thakur 2012). In this review article, we begin by defining hallmark pathological features of AD and the various forms of TBI. Putative mechanisms underlying the risk relationship between these two neurological disorders are then critically considered. Such mechanisms include precipitation and ‘spreading’ of cerebral amyloid pathology and the role of neuroinflammation. The combined problems of TBI and AD represent significant burdens to public health. A thorough, mechanistic understanding of the precise relationship between TBI and AD is of utmost importance in order to illuminate new therapeutic targets. These mechanistic investigations and the development of preclinical therapeutics are reliant upon a clear understanding of these human diseases and accurate modeling of pathological hallmarks in animal systems.